Experimental Mathematics. Volume 14, Number 3, 2005 - A K Peters (A K Peters, 2009)
On Minimal Logarithmic Signatures of Finite Groups Full TextPDF (288.8 KB) Authors Wolfgang Lempken and Tran van Trung 257-269 No access to content Irrational Life Full TextPDF (162.2 KB) Authors William Geller and Michal Misiurewicz 271-275